2010
DOI: 10.1002/jqs.1418
|View full text |Cite
|
Sign up to set email alerts
|

Aeolian dust in the Talos Dome ice core (East Antarctica, Pacific/Ross Sea sector): Victoria Land versus remote sources over the last two climate cycles

Abstract: A new ice core (TALDICE) drilled at Talos Dome (East Antarctica, Ross Sea sector) preserves a ca. 250 ka long record of palaeoclimate and atmospheric history. We investigate dust variability and provenance at the site during glacial periods and the Holocene through the Sr–Nd isotopic composition of ice core dust and potential source areas (PSA). We provide new isotopic data on dust sources from Victoria Land such as regoliths, glacial drifts, aeolian sands and beach deposits. Some of these sources are located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
148
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(164 citation statements)
references
References 40 publications
16
148
0
Order By: Relevance
“…Previous work has shown that dust deposition at TALDICE responded to large climate variations on glacialinterglacial time scales, similar to the CEAP sites, with higher fluxes during cold stages (Delmonte et al, 2010b), when TALDICE and CEAP sites had a similar dust isotopic composition, suggesting common dust sources (Delmonte et al, 2010a). On the other hand, a different dust isotopic composition between TALDICE and CEAP sites during the Holocene, together with the presence of dust grains larger than 5 µm (diameter) that were virtually absent in the EDC core, highlight the significant contribution of dust of local origins to the TALDICE dust content (Delmonte et al, 2010b).…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Previous work has shown that dust deposition at TALDICE responded to large climate variations on glacialinterglacial time scales, similar to the CEAP sites, with higher fluxes during cold stages (Delmonte et al, 2010b), when TALDICE and CEAP sites had a similar dust isotopic composition, suggesting common dust sources (Delmonte et al, 2010a). On the other hand, a different dust isotopic composition between TALDICE and CEAP sites during the Holocene, together with the presence of dust grains larger than 5 µm (diameter) that were virtually absent in the EDC core, highlight the significant contribution of dust of local origins to the TALDICE dust content (Delmonte et al, 2010b).…”
Section: Introductionmentioning
confidence: 58%
“…All sites from CEAP can be considered rather homogeneous in terms of snow accumulation rates, dust depositional fluxes, glacial-interglacial ratio of dust deposition and remote dust sources . On the other hand, the peripheries of the East Antarctic Ice Sheet are still poorly explored from this point of view (Delmonte et al, 2010b;Bory et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, so far there is no indication of such carbonate reactions in the Talos Dome ice core. Compared to other ice cores, Talos Dome shows low dust concentrations (Delmonte et al, 2010;Schüpbach et al, 2013). Furthermore, Talos Dome replicates of same depth intervals show the best quality in δ 13 C, i.e.…”
Section: Resultsmentioning
confidence: 85%
“…It is beyond the scope of this paper to discuss all these effects, nor does the current data basis yet allow firm conclusions, but there is indication that ice from the Talos Dome ice core is more reliable than from other cores. One hint for its "good ice quality" might be that its inorganic impurity content during the glacial is much lower compared to the other Antarctic ice cores (Delmonte et al, 2010), reducing the likelihood for chemical reactions and in-situ production of minute amounts of CO 2 . This feature of the coastal Talos Dome ice core can be observed as well for new N 2 O mixing ratio measurements recently obtained (Schilt et al, 2010), which showed no clear signs of in situ N 2 O production in contrast to other ice cores, like the inland cores EDML or EDC.…”
Section: Measurement Reproducibilitymentioning
confidence: 99%